Antrodin C Inhibits Epithelial-to-Mesenchymal Transition and Metastasis of Breast Cancer Cells via Suppression of Smad2/3 and β-Catenin Signaling Pathways - Kumar, K. J. Senthil; Vani, M. Gokila; Chueh, Pin-Ju; Mau, Jeng-Leun; Wang, Sheng-Yang (PloS one, 2015)
Epithelial-to-mesenchymal transition (EMT) is a crucial event involved metastasis of certain tumors. Thus, identifying chemical agents that can block EMT is highly warranted for the development of anti-cancer chemoprevention/chemotherapies. In this study, we found that Antrodin C (ADC), a maleimide derivative isolated from Antrodia cinnamomea health food product inhibits TGF-β1-induced EMT and breast cancer cell metastasis in vitro. Pretreatment of MCF-7 cells with ADC significantly blocked TGF-β1-induced phenotypic changes and actin cytoskeleton remodeling. In addition, ADC was able to up-regulate epithelial markers such as E-cadherin and occludin, whereas mesenchymal markers including N-cadherin and vimentin were significantly inhibited, possibly through the modulation of transcriptional regulators Smad/Smad3. ADC blocked TGF-β1-induced migration and invasion of MCF-7 cells through the down-regulation of matrix-metalloproteinases (MMP-2, -9) and urokinase plasminogen activator (uPA). The inhibition of MMPs and uPA activity by ADC was reasoned by suppression of its corresponding transcription factor β-catenin. Taken together, our data suggested that ADC attenuates the TGF-β1-induced EMT, migration and invasion of human breast carcinoma through the suppression of Smad2/3 and β-catenin signaling pathways.